THE INFLUENCE OF PROFESSIONAL SKEPTICISM, INDEPENDENCY, COMPETENCE, AND PERSONALITY TYPE OF AUDITORS ON THEIR ABILITY TO DETECT FRAUD - LIA WIDAYANTI DWI AGUSTIN (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The objective of this study is to assess the influence of professional skepticism, independency, competence, and personality type on auditor‟s ability to detect fraud. The data of this study was collected through questionnaires distributed to 140 convenience sampling-wise selected respondents, all of which are auditors working in non-big four public accounting firms in East Java, resulting in 108 processible data. The analysis was conducted using Partial Least Squares (PLS), finding that auditor‟s ability to detect fraud is influenced by professional skepticism, independency, and personality type and that competence does not influence the fraud detection ability. Therefore, public accounting firms should increase the ability of their auditors in detecting various forms of fraud during the audit process. This study is expected to provide considerations for the firms in placing their auditors according to their unique qualifications in order to maintain their performance.Keywords: professional skepticism, independency, competence, personality type, ability to detect fraud